Muslim Inventions and The Global Fight Against COVID-19 - Syeed, Safiyyah Sabreen (Journal of Islam and Science, 2021)
COVID-19 has wreaked havoc all across the globe, whether it be through the  rising number of cases, deaths, lockdowns, economic slowdown or just the media induced panic. In this sense we are all affected by the 'virus'. As the world grapples with this pandemic, there is a notable resonance with the past, especially between the global defense against the pandemic and the great medical  innovations of the Islamic golden age. During the Islamic scientific revolution, Muslims became pioneers in the field of medical science. Inspired by the Quran and the various Hadith that consider the science of healing a sacred endeavor, Muslims made ground breaking discoveries in different areas of medicine like anatomy, pharmacology, physiology, surgery, epidemiology and so on. These contributions led to the significant growth in the field of medical science and its various branches and went on to influence the modern medical revolution. In the present survey an effort is made to discuss the historical roots of the global medical response and measures made to combat the COVID-19 pandemic and the various significant contributions of Medieval Muslim scientists in this field.